Preparing political science students for a non-academic career: Experiences from a novel course module. (November 2019) - Broms, Rasmus; de Fine Licht, Jenny
Higher education is increasingly expected not only to provide students with disciplinary knowledge and skills but also to prepare them for a future career. As political science is a diverse discipline and does not train students for a certain profession, its students often feel uncertain of the career paths available to them and how their expertise can be used in a future career. In this article, we present and discuss the course 'The Professional Political Scientist', given at the bachelor's level at the Department of Political Science at University of Gothenburg, Sweden, which is an attempt to fill this gap. We present the preparatory work, the design, the pedagogy behind the themes and exercises included in the curriculum, as well as the experiences and evaluations of the first three rounds of the course. Finally, we provide suggestions for teachers interested in developing similar courses.